MODELLING SYNCHRONIZATION PUBLIC TRANSPORT LINES IN INTERCHANGE STOP (Perner's Contacts, 2012)
The paper deals with modelling of the synchronization of departures from the transfer stations using max-plus algebra. The problem of passengers’ transfer is formulated using mathematical max-plus algebra. In the next part of the paper there is a characteristic of Prostějov public transport and an introduction to max-plus algebra operations that are used for modelling of the synchronization of public transport lines in Prostějov.
Keywords: Synchronization, interchange stops, modelling, max-plus algebra